Reducing the Risk of Flood Disasters in Lamongan Regency Using the Geographic Information System (GIS) - Salwa Nabilah; Nur Azizah Affandy; N. Anwar; M. A. Maulana; N. Nurwatik (Kadiri University, 2021)
Flood disasters cause negative impacts, such as damage to facilities to the onset of fatalities. Reducing the risk of flooding needs to be done to reduce the impact caused by this disaster. Lamongan Regency is one of the regencies in East Java affected by floods every year in most of its areas. This study aims to reduce the risk caused by flooding by using GIS (Geographic Information System). Mitigation is done by determining areas with a high potential risk of being affected by flooding. The study used spatial analysis functions in ArcGIS. Supporting variables used rainfall, land cover, slope, soil texture, and watershed area, and it becomes important in determining flood-prone areas. From the results, the largest soil classification is the Kpl soil type. Litosol Gray Grumosol, The wide distribution of rainfall from 1500-1750 mm has the widest distribution is 66,67 ha. The slope of 0-8% has the widest distribution of 92,257 ha, making Lamongan a very vulnerable high flood area. Laren District is the District with the greatest flood potential, and Irrigated Field is the dominant land cover type affected by the flood. With the flood disaster map generated from this research, local governments can seek prevention in areas with high flood potential. They can carry out socialization based on disaster mitigation, especially for districts with potential flooding.